2012
DOI: 10.14778/2311906.2311912
|View full text |Cite
|
Sign up to set email alerts
|

Efficient reachability query evaluation in large spatiotemporal contact datasets

Abstract: With the advent of reliable positioning technologies and prevalence of location-based services, it is now feasible to accurately study the propagation of items such as infectious viruses, sensitive information pieces, and malwares through a population of moving objects, e.g., individuals, mobile devices, and vehicles. In such application scenarios, an item passes between two objects when the objects are sufficiently close (i.e., when they are, so-called, in contact), and hence once an item is initiated, it can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…As one of the most fundamental graph operators, reachability has drawn much research interest in recent years [6,36,9,34,21,10,7,20,39,37,5,35,19,8] and seems to continue fascinating researchers with new focuses [23,38,22] and new variants [15,12,31]. The basic reachability query answers whether a vertex u can reach another vertex v using a simple path (?u → v) in a directed graph.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most fundamental graph operators, reachability has drawn much research interest in recent years [6,36,9,34,21,10,7,20,39,37,5,35,19,8] and seems to continue fascinating researchers with new focuses [23,38,22] and new variants [15,12,31]. The basic reachability query answers whether a vertex u can reach another vertex v using a simple path (?u → v) in a directed graph.…”
Section: Introductionmentioning
confidence: 99%
“…• Reachability: If two people have come in close contact with each other or there exists a contact path between them through other people, we can infer one is "reachable" from the other for delivering a package, or contracting a disease [15]. • Social Strength: If two people have been to the same places at the same time, i.e., co-occurred, we can infer that they are socially connected.…”
Section: Place Frameworkmentioning
confidence: 99%
“…However, due to the nature of the utilized dataset, these studies were confined to behaviors that were observed in the online world. Recently, due to the availability of high-resolution spatiotemporal location data collected by GPS-enabled mobile devices through mobile apps, e.g., Google Maps, Facebook, Foursquare, and WhatsApp, or through online services, such as geo-tagged contents (tweets from Twitter, pictures from Instagram, Flickr or Google+ Photo), etc., it has become possible to study social behaviors by observing people's behaviors in the real world, especially via location history [15,13]. For example, if two people were seen at the same places and at the same time, i.e., cooccurred, we can infer that they are socially connected [13].…”
Section: Introductionmentioning
confidence: 99%
“…So, we should adopt the open-world assumption, admit the possibility of approximate answers, decide how to identify the relevant data sources without overloading the network (e.g., based on spatial conditions), how to route queries and results to their recipients (while preserving autonomy) using geographic routing and the physical mobility of nodes, and how to determine when a query and its associated routing tasks have to be finished. Moreover, new types of queries could be of interest in this context, requiring new query processing techniques; for example, reachability queries [36] could be used to study the possibility of propagation of a disease by analyzing past trajectories.…”
Section: Evaluation Of Global Queries On a Population Of Folk-nodesmentioning
confidence: 99%